REKONSTRUKSI PEMBANTAIAN DEIR YASSIN TAHUN 1948 DAN RELEVANSINNYA BAGI PEMBELAJARAN SEJARAH ASIA BARAT DAYA II DI PROGRAM STUDI PENDIDIKAN SEJARAH FKIP UNS - Toro, Angga Dian (Candi, 2015)
The purpose of this research were to determine: (1) the background of the Deir Yassin events in 1948, (2) the events of Deir Yassin in 1948, (3) impact of the Deir Yassin events, (4) the relevance of the Deir Yassin events by learning of Southwest Asia II History at Historical Education Program Study. This research used historical method. Source of research data was written sources both primary and secondary. Data collection techniques used were techniques literature study conducted in various libraries. The data analysis technique used was the historical analysis techniques. The steps taken in the historical method as follows: (1) heuristic, (2) criticism, (3), interprestas, (4) historiography. The results indicate that: (1) Dier Yassin events triggered by the differences between Palestinian Arabs and Jews on the history of Palestine and the defeat of the Ottoman Turks in World War I and the ideals of the Jewish State founding by Zionists, (2) Dier Yassin events in 1948 has been planned carefully through Dallet plan. Deir Yassin massacre carried out by a sudden and cruel, (3) Deir Yassin events had a politically, socially, and economically impact for the Zionists and Palestinians, (4) Dier Yassin events in 1948 was the one of historical events that occurred in the Middle East region. Deir Yassin incident should be studied more in depth. It can be inserted as a part of Palestinian problem material in Southwest Asia II Historical Course at History Education Program Study, Teacher Training and Education Faculty, Sebelas Maret University.